Protein induced lipid demixing in homogeneous membranes - Bernd Henning Stumpf; Piotr Nowakowski; Christian Eggeling; Anna Maciołek; Ana-Sunčana Smith (Physical Review Research, 2021)
Specific lipid environments are necessary for the establishment of protein signaling platforms in membranes, yet their origin has been highly debated. We present a continuum, exactly solvable model of protein induced local demixing of lipid membranes. The coupling between a local composition and a local thickness of the membrane induces lipid domains around inclusions with hydrophobic mismatch, even for temperatures above the miscibility critical point of the membrane. The model qualitatively explains the experimentally observed formation of lipid domains induced by anchoring of reconstituted actin in flat supported lipid bilayers.